Causes, effects and possible solutions of variation order in project performance - Racqueal Manggau , Donold (2013)
This thesis deals with the variation order that occurs in every construction project and how it affects the performance of the projects itself. Variation order is defined as the additions, omissions, alterations and substitution in terms of quality, quantity and schedule of works. Malaysia as a developing country is overgrown with various type of construction project here and there and the occurence of variation order in each of this project is inevitable. So, the objective of this thesis is to identify the causes of variation order in construction project, to investigate the impact of variation orders and to determine the proactive measure regarding the existence of the variation order. The scope of the study is on any ongoing construction projects in Kuantan area to identify the variation order that may occurs in each and every projects. In order to achieved the objective stated, a questionnaire is distributed to three parties involve in the construction area ; the client, consultant and contractor. Questionnaire is given according to how many projects that is still progressing handled by them. The questionnaire consists of demographic, causes of variation order, effects of variation order and the possible solution on how to avoid variation order. After 100 questionnaire is distributed and the result is tabulated, it is known that the main cause of variation order is the change of plan or scope is the main reason why variation order occurs in those construction project. It is known that the main effect of the occurence of variation order is the increase in the project cost. There will be an overrun in the cost of the project. The best possible solution to avoids variation order is to have a very good and proactive communication between all parties (the clients, contractors and consultants) throughout the construction of the project from start to finish. In a nutshell, it is known that the client, contractor and also the consultant all played a vital and important role in order to have a zero variation order or at least to minimize the variation order itself in each of the projects that are handled by them. Variation order should be taken as a serious matter as it will affects the project performances and also the growth of development in Malaysia in a long term period of time.